Diritto, politica, neuroscienze - Sammicheli, Luca (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2021)
Neurolaw is beginning to have a few years of ‘seniority’ in debate but some ambiguities still seem to characterize its boundaries. In this work we will try to retrace some of them. First of all, we will try to investigate the different conceptual dimensions of the term ‘neuroscience’: I) neuroscience as an epistemological domain at various levels; II) behavioral neuroscience, or ‘neuropsychology’, as a particular method of studying behavior; III) neuro-reductionism and the foundations of behavioral sciences. From these ideas we will then try to investigate a more general theme, that is the alleged ‘apolitical’ of science. Finally, a particular variation of this will be exposed, namely the substantial ‘political nature’ of the scientific concept of ‘mental disorder’ (as defined in the latest edition of the DSM) and its repercussions on law.